Jahrbuch für Germanistische Sprachgeschichte (De Gruyter, 2012)
Jahrbuch für germanistische Sprachgeschichte (Yearbook for German Language History) is a periodical devoted to the contents, methods and objects of language history research and their relevance in present-day German Studies, thus providing a forum for current research papers. The conception of the yearbook is derived from the purposes of the Association for German Language History, and it serves as their principal publication.